Innovative strategies for accelerated human resource development in South Asia information and communication technology for education special focus on Bangladesh, Nepal, and Sri Lanka. (Metro Manila, Philippines Asian Development Bank, 2017)
Information and communication technology (ICT) has the potential to revolutionize education equity, quality, and efficiency. South Asia governments have recognized this potential and invested in ICT focused education initiatives and projects. While these efforts helped to introduce ICT enabled teaching and learning practices, they may not be sufficient for widespread sustainable adoption within their countries. The stage of implementation and impact of investments also vary significantly from country to country in South Asia.
Keywords: Education -- Economic aspects -- South Asia; Information technology -- South Asia; Electronic books